The global World through Unamuno (Res Publica. Revista de Historia de las Ideas Políticas, 2019)
The globalized world, subject to an acceleration that produces innumerable alterations, is putting an end to the traditional common space. New forms of community organization establish identities that alter the mode of relationship. A critical revision of modern assumptions is essential for the establishment of a conceptualization appropriate to the present demands. In this sense, the work of Miguel de Unamuno serves as an intellectual stimulus to reveal the contradictions inserted in the global political drift.